Forget unlearning? How an empirically unwarranted concept from psychology was imported to flourish in management and organisation studies. Issue 4 (September 2016) - Howells, John; Scholderer, Joachim
We provide a critique of the development in organisation studies of the idea of 'unlearning' as allegedly imported from the psychology literature by Hedberg and understood to mean the manageable discard of knowledge precedent to and aiding later learning. We re-review the psychology literature and in contrast to Hedberg, find that this definition of unlearning is not empirically warranted. We re-examine a selection of highly cited articles in the organisational literature that claim to have conducted empirical research into the Hedberg model of unlearning. We find none provide evidence of its existence. Typically, under the label 'unlearning' evidence is provided of a conventional process of theory-change, the setting aside (not deletion) of an established understanding in favour of new understanding when presented with perceived new facts. In all cases that we examine, clear alternative and less problematic concepts should provide a better conceptual framework for the research, such as learning, theory-change, discard of practice and extinction. It follows that the unlearning literature is not in fact the independent, scholarly and scientific literature that many of its adherents believe it to be. We recommend that for concepts allegedly imported from other disciplines more frequent commissioning of cross-disciplinary reviews may encourage the critical works so obviously lacking in the unlearning literature.